Price Dispersion in the Government Securities Market - Garbade, Kenneth D.; Silber, William L. (Journal of Political Economy, 1976)
This paper investigates the characteristics of price dispersion in the U.S. Treasury securities market. After a theoretical treatment of why such dispersion exists, empirical evidence is presented which shows that dispersion is influenced by characteristics of securities (such as volume and maturity) and by market supply-demand conditions (as reflected in price-level changes). It is also shown that the cost of liquidity services in a competitive market is determined by price dispersion and is not equal to the bid-ask spread.